2012
DOI: 10.1093/eurpub/cks123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between antenatal care and preterm birth: the importance of content of care

Abstract: This study suggests that measurement of the content and timing of care of antenatal care using the new CTP tool is a better assessment of the risk of preterm birth than assessment of the number of antenatal visits alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 24 publications
13
56
0
8
Order By: Relevance
“…These results corroborate other studies that have also found a higher proportion of inadequate prenatal care for women with unfavorable characteristics, such as ethnicity/black and brown skin color (24) , who did not plan their pregnancy and unmarried, which tend to start Prenatal care late and perform fewer visits (1,(25)(26)(27) . Also, there was association of inadequate prenatal care to mothers who have made combined prenatal care (OR=3.9 in the univariate analysis and AOR=5.7 in the multivariate analysis).…”
Section: Discussionsupporting
confidence: 90%
“…These results corroborate other studies that have also found a higher proportion of inadequate prenatal care for women with unfavorable characteristics, such as ethnicity/black and brown skin color (24) , who did not plan their pregnancy and unmarried, which tend to start Prenatal care late and perform fewer visits (1,(25)(26)(27) . Also, there was association of inadequate prenatal care to mothers who have made combined prenatal care (OR=3.9 in the univariate analysis and AOR=5.7 in the multivariate analysis).…”
Section: Discussionsupporting
confidence: 90%
“…A prospective cohort study by Beeckman K et al also concluded that timely and accurate antenatal screening is believed to be an important factor in preventing preterm birth. 10 Multiparity was an independent risk factor for higher rates of preterm birth in our study, as 47.5% multiparous females had preterm deliveries. Sabiri N in her study summarised that the risk factors for preterm birth were, low level of maternal education (p <0.004), absence of pregnancy monitoring (<0.001), multiparity (p <0.001) and maternal chronic disorders (p <0.001).…”
Section: Discussionsupporting
confidence: 51%
“…It is believed that timely and correct antenatal care prevents premature birth. In a study conducted in France, more premature births were reported in mothers who had not been examined in the first 3 months of pregnancy and who had had fewer [22]. In the current study, the rates of premature birth were similar between those who had fewer than or more than 4 visits and those who presented early or late (p=0.643).…”
Section: Discussionsupporting
confidence: 63%